Historical retrospective for development of agricultural administration in Ukraine (1995 – 2015) - Belova, O. I. (History of science and technology, 2018)
The reforms in the agriculture of independent Ukraine have generated a large number of new private landowners and users. A significant part of them - farmers, owners of private peasant farms - have an inadequate level of agricultural knowledge, in particular, with regard to the use of the latest technologies in crop and livestock production. Therefore, they need professional assistance, advice and raising the level of agricultural knowledge. Such services are elements of agricultural advisory services as a separate activity in agriculture. The author analyzes the stages of develop-ment of agricultural advisory activity in Ukraine and proposes directions for its improvement.